Evaluation of amoebicidal potential of Paneth cell cryptdin-2 against Entamoeba histolytica. - Simran Preet; Sanjay Bharati; Geeta Shukla; Ashwani Koul; Praveen Rishi (PLoS Neglected Tropical Diseases)
Background Amoebiasis is a major public health problem in tropical and subtropical countries. Currently, metronidazole is the gold choice medication for the treatment of this disease. However, reports have indicated towards the possibility of development of metronidazole-resistance in Entamoeba strains in near future. In view of the emergence of this possibility, in addition to the associated side effects and mutagenic ability of the currently available anti-amoebic drugs, there is a need to explore newer therapeutics against this disease. In this context, the present study evaluated the amoebicidal potential of cryptdin-2 against E. histolytica. Methods/principal findings In the present study, cryptdin-2 exhibited potent in-vitro amoebicidal activity against E. histolytica in a concentration dependent manner at a minimum amoebicidal concentration (MAC) of 4 mg/L. Scanning electron microscopy as well as phase contrast microscopic investigations of cryptdin-2 treated trophozoites revealed that the peptide was able to induce significant morphological alterations in terms of membrane wrinkling, leakage of the cytoplasmic contents and damaged plasma membrane suggesting a possible membrane dependent amoebicidal activity. N-phenyl napthylamine (NPN) uptake assay in presence of sulethal, lethal as well as twice the lethal concentrations further confirmed the membrane-dependent mode of action of cryptdin-2 and suggested that the peptide could permeabilize the plasma membrane of E. histolytica. It was also found that cryptdin-2 interfered with DNA, RNA as well as protein synthesis of E. histolytica exerting the highest effect against DNA synthesis. Thus, the macromolecular synthesis studies correlated well with the observations of membrane permeabilization studies. Significance/conclusions The amoebicidal efficacy of cryptdin-2 suggests that it may be exploited as a promising option to combat amoebiasis or, at least, may act as an adjunct to metronidazole and/or other available anti-amoebic drugs.